APPLICATION OF PIEZODISC AS A SENSOR FOR STRUCTURALHEALTH MONITORING - Rupali Jadhav; Pawan Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper mainly focuses on the development of piezo electric material as a sensor for crack detection for different materials. Now a days the field of smart material is introduced in the market. Major applications of piezoelectric sensors are in aircraft structure monitoringsystems, Ship structures and maintenance, civil structures, non destructive testing for heavy machines and in manufacturing processes. Smart material is the new technology which having the capability of both sensing and actuation, and to achieve this at lower cost, integrating the system with compact design, with less complexity and having good reliability.Piezoelectric materials is the most attractive functional materials for sensors and actuators because they can directly convert mechanical energy into electrical energy and vice versa.The application of transmitter-sensor pair of Piezoelectric material for crack detection.